PENDEKATAN SAVI SEBAGAI METODE ALTERATIF UNTUK MEMAKSIMALKAN GAYA BELAJAR SISWA SEKOLAH DASAR - Mahmudah Titi Muanifah; Halimah Sa’diyah (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: Learning style is one of the factors affecting success in a learning process associated with student. Therefore, teachers need to make an innovation on learning process, so that students' learning styles can be optimized. SAVI approach (Somatic, Auditory, Visual, and Intellectual) is a learning approach that is expected to make a good contribution in order to improve students' learning outcomes, especially in mathematics subject. Due to the process of learning mathematics using SAVI approach, students’ senses are employed in learning so their learning style can be maximized. In addition, the use of SAVI approach can also be an alternative learning approach that is active and fun for students.